2023
DOI: 10.1007/s00167-023-07349-4
|View full text |Cite
|
Sign up to set email alerts
|

Majority of competitive soccer players return to soccer following hip arthroscopy for femoroacetabular impingement: female and older aged players are less likely to return to soccer

Abstract: Purpose To determine return to soccer rates and soccer performance in a large cohort of competitive soccer players after hip arthroscopic surgery for the treatment of femoroacetabular impingement (FAI) and to identify possible risk factors associated with not returning to soccer. Methods An institutional hip preservation registry was retrospectively reviewed for patients identiied as competitive soccer players who underwent primary hip arthroscopy for FAI performed between 2010 and 2017. Patient demographics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Marom et al 50 2023 87 competitive soccer players (119 hips)-75% of players returned to soccer, 49% of whom returned at the same level Bilateral hip surgery was not a risk factor for RTP; however, female players and older patients returned at lower rates than male and younger patients Anari et al 53 2023 83 high-level soccer athletes-85% of whom returned to the sport in the first or second season after surgery Only 37% of the athletes returned to performing in 80% of the games 1 y after surgery compared with the last asymptomatic season Saito et al 54 2019 28 soccer players undergoing hip arthroscopy-92% of players returned to soccer at the same or higher level at a median of 5.5 mo 51 Prevalence of tenderness at the pubic symphysis decreased from 32% preoperatively to 3% postoperatively RTP indicates return to play.…”
Section: Postoperative Rehabilitationmentioning
confidence: 99%
“…Marom et al 50 2023 87 competitive soccer players (119 hips)-75% of players returned to soccer, 49% of whom returned at the same level Bilateral hip surgery was not a risk factor for RTP; however, female players and older patients returned at lower rates than male and younger patients Anari et al 53 2023 83 high-level soccer athletes-85% of whom returned to the sport in the first or second season after surgery Only 37% of the athletes returned to performing in 80% of the games 1 y after surgery compared with the last asymptomatic season Saito et al 54 2019 28 soccer players undergoing hip arthroscopy-92% of players returned to soccer at the same or higher level at a median of 5.5 mo 51 Prevalence of tenderness at the pubic symphysis decreased from 32% preoperatively to 3% postoperatively RTP indicates return to play.…”
Section: Postoperative Rehabilitationmentioning
confidence: 99%
“…Females (i.e., individuals identified as female sex at birth) comprise two‐thirds of the individuals diagnosed with or treated for FAI syndrome (pain in the presence of cam or pincer morphology and clinical signs) 1,20–22 . Compared to males, females with FAI syndrome report worse pain and functional deficits, 23,24 have poorer surgical outcomes, 25–27 and are less likely to return to sport following treatment 27,28 . The high prevalence combined with poorer outcomes expose a critical need for female‐focused studies to determine if and when cam morphology develops in the female athlete.…”
Section: Figurementioning
confidence: 99%
“…Femoroacetabular impingement syndrome (FAIS) is a common cause of hip and groin pain in athletes. It is even more common in sports with high demands on the hip joint, such as ice hockey and soccer, 8,9,12,16 and studies have shown a higher prevalence of radiological cam morphology in athletes performing these types of sports. 7,13 In both ice hockey and soccer, athletes put high loads on their hip joints and perform repetitive movements such as rapid change of direction, internal rotation, adduction, and deep hip flexion that potentially provoke symptoms that are associated with FAIS.…”
mentioning
confidence: 99%
“…8,11 Hip arthroscopy is a treatment option for athletes with FAIS that has shown favorable outcomes in terms of pain relief and patient satisfaction. 9,12 Studies have further shown high rates of return to sports (RTS) (87%-93%). 14,18 However, there is a large discrepancy between reported rates of RTS to preinjury performance level (21%-83%) depending on the definition used.…”
mentioning
confidence: 99%
See 1 more Smart Citation